Extensor Retinaculum Reconstruction of the Distal Radioulnar Joint in Adolescents. (September 2022) - Bauer, Andrea S.; Lee, Stella J.; Smith, Michael D.; Bae, Donald S.; Waters, Peter M.
Background: This study characterizes the outcomes and complications of surgical reconstruction of distal radioulnar joint (DRUJ) instability using the extensor retinaculum (Herbert sling). Our hypothesis was that extensor retinaculum reconstruction is a reliable method of DRUJ stabilization in adolescents. Methods: This was a retrospective study of pediatric patients treated surgically using the Herbert sling for DRUJ instability at a single institution. We identified 22 subjects who underwent surgery at an average of 16.2 years of age (range, 12-18 years). Medical records and available imaging were reviewed for all subjects, and patients were contacted to participate in the prospective completion of the Quick Disabilities of the Arm, Shoulder, and Hand (QuickDASH) questionnaire. Results: Preoperative symptoms were more commonly pain (95%) than feelings of DRUJ instability (45%), although 100% had instability on physical examination. Eight (36%) patients demonstrated limited supination preoperatively. Twenty-one subjects (95%) noted prior injury to that wrist, 15 of which were distal radius fractures. Surgery consisted of stabilization of the DRUJ using extensor retinaculum, in concert with other procedures to address all potential causes of wrist pain. Postoperatively, DRUJ stability was maintained in 21 of 22 subjects. Of the 12 patients who provided functional outcome scores, median QuickDASH score was 7.6 (range, 0-45). Conclusions: Distal radioulnar joint instability in adolescents is often preceded by fracture of the distal radius. Surgeons must maintain a high level of suspicion to appropriately diagnose DRUJ instability, which is often not an isolated pathoanatomical problem. The Herbert sling technique using extensor retinaculum can successfully confer DRUJ stability in this population.